Innovation Of Amaly Interpretation Learning At Primaganda Senior High School Jombang - Moch. Sya'roni Hasan; Mar'atul Azizah (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
This study aims to describe the learning innovation of Tafsir Amaly at SMA Primaganda Jombang. Tafsir Amaly is a local content subject that is included in the Primaganda High School curriculum. Tafsir Amaly is a Sufism-based interpretation developed by Thoriqoh Syadziliyah Al Mas'udiyah Jombang. This type of research uses a qualitative approach. Data collection methods: observation, interviews, and documentation. Technical analysis includes data reduction, data presentation, and concluding. To check the validity of the data, research extension, observation persistence, and triangulation were used. The results showed that the innovation of the implementation of Amaly's Tafsir includes the application of a combination of student-centered and conventional methods in the form of jigsaw cooperative methods, drills, discussions, questions and answers, peer tutorials, exemplary affective methods, and so on supported by the book Tafsir Amaly juz 1 and Quran song as a compliment. Then the teaching aids use qurany 1-5 if needed according to the learning theme of Amaly's Tafsir, Then the learning media can be supported by other means, for example, audio speakers, and so on.